Frugal innovation in Germany: A qualitative analysis of potential socio-economic impacts - Rajnish Tiwari; Luise Fischer; Katharina Kalogerakis (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2017)
Frugal innovation is gaining traction globally, not only in emerging economies, but also in the industrialized world. The root causes of frugality's acceptance as a societal value may however differ according to the social context, especially between the developing and the developed world. In this paper we present the results of a trend analysis in Germany that has been conducted as a part of a BMBF-supported project aiming to investigate "Potentials, Challenges and Societal Relevance of Frugal Innovations in the Context of Global Innovation Competition". The research was conducted in two steps. In a first step preliminary insights were generated by an extensive literature review and 3 focus groups with 30 experts discussing the relevance of frugal innovation for Germany. These insights were then verified in 20 semi-structured interviews with additional experts from cross-sections of the German society. The experts opined that frugal products and services (should) focus on the customers' core needs and reduce unnecessary complexity while adhering to high quality standards. They predicted a trend towards frugal solutions in Germany due to a complex interplay of various factors. One notable factor was a growing appreciation of moderation and voluntary simplicity by parts of the German society leading to "frugal choices". The second widespread consensus was that frugal innovations are necessary to secure long-term competitiveness of German companies in fast-growing, unsaturated markets in the emerging economies. Several challenges were pointed out concerning the actual implementation of frugal concepts in the product development process. An overwhelming reliance on high tech-driven and complexity-embracing innovation pathways by engineers in German firms was characterized as a powerful obstacle in implementing frugality.
Keywords: 330; Frugal Innovation; Germany; Affordability; Moderation; Emerging Markets; Voluntary Simplicity; Affordable Excellence; Frugality 3.0